Transparency, Social Media Exposure and Citizen Engagement: Evidence From Indonesia’s Free Nutritious Meal Program in Bogor City - Annory Langga'o; Roni Jayawinangun; Feri Ferdinan Alamsyah (CV. Ulil Albab Corp, 2026)
Indonesia's Free Nutritious Meal Program (Makan Bergizi Gratis, MBG) has generated intense public discourse, yet it remains unclear whether public participation rests more on the perceived transparency of official information or on the volume of programme-related content citizens encounter on social media. This study compares the two pathways within a single explanatory model. A cross-sectional survey of 243 residents of Bogor City measured perceived government information transparency, social media content exposure, and a composite participation index covering programme acceptance, participation intention, and digital participation. The data were analysed using Pearson correlation, standard multiple regression, and a Hotelling-Williams test for the difference between two dependent, overlapping correlations. Both transparency and exposure independently predicted participation, but transparency held a significantly stronger association with participation than exposure did, and this ordering was preserved when extreme scores were trimmed. Beneficiary status, whether direct or through a family member, did not differentiate participation. The findings indicate that the clarity, accuracy, and accessibility of official information matter more than the sheer volume of online content in shaping public participation, offering practical guidance for allocating public communication resources around flagship social programmes.